STERNOMASTOID RUPTURE AN INDEX OF ANTEMORTEM HANGING - AN AUTOPSY STUDY OF HUNDRED CASES (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Hanging remains to be one of the common methods of committing suicide. Homicidal and accidental hanging is rare1, 2 . Hence all cases of hanging are considered suicidal until the contrary is proved3.Because of the above, postmortem suspension of the body may be resorted to cloak a crime. Therefore meticulous dissection and sharp distinction between ante mortem hanging and postmortem suspension is warranted.
Keywords: sympathique; Vertical salivary